A Pendeteksian Financial Statement Fraud menggunakan Fraud Pentagon Pada Perusahaan Pertambangan Terdaftar Di BEI Tahun 2018-2020 - Dian catur hidayat; Triyono Triyono (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2022)
Financial statement fraud is the fraud that is carried out by displaying financial statements that are not by actual events. The reason for doing financial statement fraud is to make stockholders believe that the performance of the company is satisfactory. In facilitating its actions, it can be done by presenting annual financial statements that are better than the original, such as increasing profits and reducing debt. The purpose of this study is to identify opportunities for financial statement fraud to occur using the fraud pentagon model theory developed by Crowe Howarth in 2012. In the fraud Pentagon model, there are five main variable elements, namely pressure, opportunity, rationalization, ability, and arrogance. The population and sample in this study use annual reports from mining sector companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2020 period. The data used is secondary data by obtaining it from the company's official website and the Indonesia Stock Exchange (IDX) website. Through the purposive sampling method, 32 companies were selected as samples. The multiple regression analysis methods was chosen to analyze the data assisted by the SPSS 21 program. The results of this study indicate that the ineffective monitoring variable as measured by the comparison of the board of commissioners influences on financial statement fraud. Meanwhile, other variables such as financial target, external pressure, nature of industry, Rationalization, Capability, and Arrogance do not affect on financial statement fraud.